Cross-Modal Functional Reorganization of Visual and Auditory Cortex in Adult Cochlear Implant Users Identified with fNIRS - Ling-Chia Chen; Pascale Sandmann; Jeremy D. Thorne; Martin G. Bleichner; Stefan Debener (Neural Plasticity)
Cochlear implant (CI) users show higher auditory-evoked activations in visual cortex and higher visual-evoked activation in auditory cortex compared to normal hearing (NH) controls, reflecting functional reorganization of both visual and auditory modalities. Visual-evoked activation in auditory cortex is a maladaptive functional reorganization whereas auditory-evoked activation in visual cortex is beneficial for speech recognition in CI users. We investigated their joint influence on CI users’ speech recognition, by testing 20 postlingually deafened CI users and 20 NH controls with functional near-infrared spectroscopy (fNIRS). Optodes were placed over occipital and temporal areas to measure visual and auditory responses when presenting visual checkerboard and auditory word stimuli. Higher cross-modal activations were confirmed in both auditory and visual cortex for CI users compared to NH controls, demonstrating that functional reorganization of both auditory and visual cortex can be identified with fNIRS. Additionally, the combined reorganization of auditory and visual cortex was found to be associated with speech recognition performance. Speech performance was good as long as the beneficial auditory-evoked activation in visual cortex was higher than the visual-evoked activation in the auditory cortex. These results indicate the importance of considering cross-modal activations in both visual and auditory cortex for potential clinical outcome estimation.